1990
DOI: 10.1007/bf00307661
|View full text |Cite
|
Sign up to set email alerts
|

The risk of convulsions: a longitudinal study of normal babies and infants with neonatal damage in the first 6 years of life

Abstract: After carefully reviewing the epidemiological literature on this subject, we assessed the risk of febrile, isolated or epileptic convulsions in normal babies and infants with neonatal damage. We considered 417 term or preterm infants with birth injury and compared them with 400 healthy full-term newborns, all born between 1978 and 1980, studying each one individually until at least the age of 6 using the chi 2 test, the risk factors in relation to the convulsive outcome in all the groups were processed. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A case–control study from Germany[12] showed that elderly mother, previous abortions, eclampsia, low birth weight, asphyxia, and post maturity were associated with epilepsy. An Italian follow-up study[13] recognizes asphyxia and neurological syndromes to be important in developing epilepsy in children. Another incident case–control study from Sweden[14] had shown that maternal hypertension (OR 4.8), Apgar score <6 (OR 3.8), abnormal gestational age (OR 6.7), and caesarean section (OR 18) were associated with childhood epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…A case–control study from Germany[12] showed that elderly mother, previous abortions, eclampsia, low birth weight, asphyxia, and post maturity were associated with epilepsy. An Italian follow-up study[13] recognizes asphyxia and neurological syndromes to be important in developing epilepsy in children. Another incident case–control study from Sweden[14] had shown that maternal hypertension (OR 4.8), Apgar score <6 (OR 3.8), abnormal gestational age (OR 6.7), and caesarean section (OR 18) were associated with childhood epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Infants suffering from episodes of apnoea and bradycardia in the neonatal period are suggested to have an increased incidence of diplegia and other neurological handicaps (Bacola et al 1966) such as an increased risk for convulsion in infants up to six years (Tudehope et al 1986). Up to two years persistent neonatal apnoea appears to be associated with no higher incidence of significant developmental problems (Nalin et al 1990) and with no additional deleterious effect on average intellectual performance though it may be an important causative factor in functional handicap (Koons et al 1993). Furthermore, apnoea has been documented to have a relationship to school age development (Taylor et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, it is well known that newborns without MMC who develop CE in combination with IH are also at increased risk for neurocognitive impairment, compared to those who do not develop IH [15,16] . Furthermore, the occurrence of severe apneic episodes independently of the presence or absence of seizures has been shown to be associated with adverse neurodevelopmental outcome [13] . We speculate that the development of these complications contributed significantly to the observed adverse neurocognitive outcome in our cohort, based on the more favorable fi ndings in fMMC children who developed seizures without such complications.…”
mentioning
confidence: 99%